Polycentric governance model for transformative adaptation in Morocco: Transformative adaptation options - Amarnath, Giriraj; Ait El Mekki, Abdelkader; Amarasinghe, Upali; Saleth, Rathinasamy Maria; Brouziyne, Youssef (CGIAR System Organization, 2022)
This paper developed an inventory of adaptation options implemented in the last two decades in Morocco. The agricultural development strategies and plans, set up since the early 2000s, targeting investments to modernize different economic sectors, were the Rural development strategy (RDS, 2008-2008), Green Morocco Plan (GMP, 2008-2020), and Generation Green (GG, 2022-2030). The GMP comprised a slew of adaptation options to address the climate risks and new socio-economic challenges with public and private participation. The main adaptation options were 1). National program for the Supply of Drinking and Irrigation water, 2). Restoration and rehabilitation of small and medium hydraulic périmètres in all agroecological zones, 3). Adoption of a multi-task climate insurance program, 4). Conversion of vulnerable crop area to crop with high climate adaptability, 4). Development of genetically improved plant varieties to cope with drought and water scarcity, 5). Supporting supplemental irrigation in water deficit regions, and 6). Grant program for farmers to access technologies for climate adaptation. The paper concludes with an assessment of the transformative nature of adoption options.